Exploring newer cardioprotective strategies: ω-3 fatty acids in perspective - Di Minno, Matteo Nicola Dario; Tremoli, Elena; Tufano, Antonella; Russolillo, Anna; Lupoli, Roberta; Di Minno, Giovanni (Thrombosis and Haemostasis, 2010)
In the 1980s, observational retrospective studies showed an inverse relation between coronary heart disease (CHD) and consumption of fish containing fatty acids that belong to the omega (ω)-3 family. Large case-control studies and prospective intervention trials consistently showed that ω-3 fatty acids supplementation lowers fatal myocardial infarction (MI) and sudden cardiac death. By analysing the strengths of the results of individual studies and how the meta-analyses agree with them, putting together relevant backgrounds, and identifying open questions, the following findings/directions emerge. (i) Dietary and non-dietary intake of ω-3 fatty acids reduces overall mortality, mortality due to MI, and sudden death in patients with CHD; (ii) Fish oil consumption directly or indirectly affects cardiac electrophysiology. Fish oil reduces heart rate, a major risk factor for sudden death; (iii) Among patients with implantable cardioverter defibrillators, ω-3 fatty acids do not reduce the risk of ventricular tachycardia/ventricular fibrillation and may actually be pro-arrhythmic; (iv) The consumption of ω-3 fatty acids leads to a 10–33% net decrease of triglyceride levels. The effect is dose-dependent, larger in studies with higher mean baseline triglyceride levels, and consistent in different populations (healthy people, people with dyslipidaemia, diabetes, or known cardiovascular risk factors); (v) Outcomes for which a small beneficial effect ω-3 fatty acids is found include blood pressure (about 2 mmHg reduction), re-stenosis rates after coronary angioplasty (14% reduction), and exercise tolerance testing. Major experimental data provide strength (biological plausibility) for these findings, and define directions for newer clinical trials with ω-3 fatty acids.
Keywords: Prevention; acute myocardial infarction; nutrition